2009
DOI: 10.2340/00015555-0653
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Urticaria is Usually Associated with Fibromyalgia Syndrome

Abstract: Although the pathophysiology of chronic urticaria is not fully understood, it is possible that dysfunctioning of peripheral cutaneous nerve fibres may be involved. It has also been suggested that fibromyalgia syndrome, a multi-symptomatic chronic pain condition, may be associated with alterations and dysfunctioning of peripheral cutaneous nerve fibres. The aim of this study was to determine whether patients with chronic urticaria are also affected by fibromyalgia syndrome. A total of 126 patients with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
0
23
2
7
Order By: Relevance
“…24 However, to the best of our knowledge, there is no study regarding FMS frequency in acne patients. Torresani et al 21 found that 70.6% of patients with chronic urticaria had FMS, but this study did not address FMS-related symptoms. Yener et al 22 reported that the frequency of FMS was similar between the chronic urticaria patients and healthy controls.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…24 However, to the best of our knowledge, there is no study regarding FMS frequency in acne patients. Torresani et al 21 found that 70.6% of patients with chronic urticaria had FMS, but this study did not address FMS-related symptoms. Yener et al 22 reported that the frequency of FMS was similar between the chronic urticaria patients and healthy controls.…”
Section: Discussionmentioning
confidence: 96%
“…A literature search revealed that there are three published studies regarding FMS frequency in chronic urticaria, [21][22][23] and one study in psoriasis. 24 However, to the best of our knowledge, there is no study regarding FMS frequency in acne patients.…”
Section: Discussionmentioning
confidence: 99%
“…FMS patofizyolojisi henüz tam olarak açıklığa kavuşmamış olup son zamanlarda FMS'de periferal sinirlerin rolünün geçmişte düşünülenden daha fazla olduğu kabul edilmektedir 8 . FMS'nin periferal kutanöz sinir liflerinin değişikliği veya disfonksiyonu ile ilişkili olabileceği düşünülmektedir 9 . FMS'li hastaların deri biyopsilerinde artmış nörojenik inflamasyonla uyumlu bulguların saptanmış olması FMS patogenezinde nörojenik inflamasyonun rol oynadığı görüşünü desteklemektedir 10 .…”
Section: Introductionunclassified
“…Bu nörojenik inflamasyonun yine etyolojisi benzer şekilde tam olarak açıklığa kavuşmamış olan kronik ürtiker patogenezinde de rol oynayabileceğine dair çalışmalar mevcuttur 8 . Bu ortak hipotezden yola çıkarak yakın dönemde yapılmış olan bir çalışmada, kronik ürtikeri olan hastalarda fibromiyalji sendromu sıklığı normal toplumdan çok daha yüksek bulunmuştur 9 . Ayrıca, fibromiyalji sendromunda olduğu gibi kronik ürtiker etyolojisinde de emosyonel stresin önemli bir rol oynadığı düşünülmektedir 10 .…”
Section: Introductionunclassified
“…Ayrıca, fibromiyalji sendromunda olduğu gibi kronik ürtiker etyolojisinde de emosyonel stresin önemli bir rol oynadığı düşünülmektedir 10 . Ancak, kronik ürtiker ile fibromiyalji sendromunun birlikteliğini inceleyen İngilizce literatürde sadece bir çalışma mevcuttur 9 . Yukarıda bahsi geçen bilgiler doğrultusunda, biz bu çalışmada hem etyolojide hem de patogenezde ortak noktaları olduğu bilinen bu iki hastalığın birlikteliğini araştırmayı ve bu birlikteliğin hastalık şiddetinden etkilenip etkilenmediğini belirlemeyi amaçladık.…”
Section: Introductionunclassified